2019
DOI: 10.11648/j.sjc.20190704.12
|View full text |Cite
|
Sign up to set email alerts
|

2-oxo-2H-chromen-3-yl Propionate and 2-oxo-2H-chromen-3-yl Acetate: Short-step Synthesis, Characterization and Fluorescence Properties

Abstract: Natural or synthetic coumarins are of great interest, since many of them show prominent biological activity and photochemical characteristics. In particular, hydroxycoumarins and their derivatives have been extensively studied in various fields such as biology, medicine, physics and chemistry. Among the well-known compounds is 7-hydroxycoumarin, also known as umbelliferone and 4-hydroxycoumarin. Against 3-hydroxycoumarin and its derivatives are less known and studied. In this study, new acyl derivatives were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This is the case for carboxylates of 4-hydroxycoumarin [40][41][42] and 7-hydroxycoumarin [43][44][45][46]. In the case of 3-hydroxycoumarin, the crystalline structure has been established for compounds 30b, 30c, 30d, 30e, 30g, 30j, 30h [6][7][47][48][49][50][51]. The crystallographic data are here reported for compound 30b, 30e, 30g, 30h.…”
Section: Synthesis Of 3-coumarinyl Carboxylatesmentioning
confidence: 89%
See 4 more Smart Citations
“…This is the case for carboxylates of 4-hydroxycoumarin [40][41][42] and 7-hydroxycoumarin [43][44][45][46]. In the case of 3-hydroxycoumarin, the crystalline structure has been established for compounds 30b, 30c, 30d, 30e, 30g, 30j, 30h [6][7][47][48][49][50][51]. The crystallographic data are here reported for compound 30b, 30e, 30g, 30h.…”
Section: Synthesis Of 3-coumarinyl Carboxylatesmentioning
confidence: 89%
“…Previous work has shown that phenols, particularly hydroxycoumarins and some similar compounds such as homophthalic anhydrides, are suitable for acylation reactions with different results. Indeed, in the case of homophthalic anhydride, there is only C-acylation, where as in the case of hydroxycoumarin derivatives, acylation could be either O-acylation or C-acylation [6][7]32]. Several acylation processes for compound 1 have been described.…”
Section: Synthesis Of 3-coumarinyl Carboxylatesmentioning
confidence: 99%
See 3 more Smart Citations